Pengaruh Edukasi terhadap Pengetahuan Pasien Tuberkulosis tentang Penyakit Menular dalam Meningkatkan Efektivitas Pengobatan Tuberkulosis di Puskesmas Kabupaten Bekasi - Dewi, Masita Sari; Adiwisastra, Nuzul Gyanata; Ulfah, Ulyati (Universitas Pahlawan Tuanku Tambusai, 2025)
Tuberculosis is one of the most prevalent infectious diseases in Indonesia. Patient knowledge about the disease plays a crucial role in the success of treatment, particularly in improving adherence and the effectiveness of therapy. The duration of treatment is often a source of complaint among patients, leading to irregular medication intake or even forgetting to take medication, which hinders treatment success. The community service activity conducted at the Mekarmukti Health Center is one of the efforts to improve knowledge and adherence to treatment. The activity was attended by 23 participants who were tuberculosis patients and were accompanied by health center cadres. The method used in presenting the material was a lecture using flip charts. The activity was evaluated through the completion of pretest and posttest forms by the participants. The evaluation results showed a significant difference from the pretest score of 75.65% to the posttest score of 88.69%. This improvement in evaluation results serves as a parameter for the success of this activity. It is hoped that this activity will contribute to the success of treatment and also encourage the dissemination of information to the families and communities surrounding tuberculosis patients.